Strategic Resilience in Agribusiness: Does CSR Moderate Financial Risks in Indonesian Palm Oil Firms? - Pardomuan Sihombing; Ratih Dwi Asmaranti (Research of Finance and Banking, 2026)
This study examines the critical role of Corporate Social Responsibility (CSR) in shaping firm value in the palm oil industry, a sector under intense global environmental and social scrutiny. As one of the most controversial resource-based industries, palm oil companies are frequently linked to deforestation, climate change, biodiversity loss, and social conflicts, which significantly influence stakeholder perceptions and investor confidence. These conditions create a fundamental problem: firms with strong financial performance may still experience a gap between their operational achievements and market valuation due to external pressures. Therefore, CSR in this context is no longer merely a symbolic or ethical obligation, but a strategic necessity to maintain legitimacy, enhance corporate reputation, and ensure long-term sustainability. This study examines how internal financial factors, including financial performance, capital structure, profit growth, and operating cash flow, affect firm value while incorporating CSR as a moderating variable. By doing so, the research provides a more comprehensive understanding of firm value that integrates both financial and non-financial dimensions. Ultimately, this study highlights that in high-risk industries such as palm oil, sustainable value creation depends not only on financial strength but also on a company's commitment to responsible environmental and social practices